2019
DOI: 10.1021/acs.jmedchem.8b01704
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Cyclometalated Iridium(III) Complexes with Planar Ligands: Mitochondrial DNA Damage and Metabolism Disturbance

Abstract: Emerging studies have shown that mitochondrial DNA (mtDNA) is a potential target for cancer therapy. Herein, six cyclometalated Ir­(III) complexes Ir1–Ir6 containing a series of extended planar diimine ligands have been designed and assessed for their efficacy as anticancer agents. Ir1–Ir6 show much higher cytotoxicity than cisplatin and they can effectively localize to mitochondria. Among them, complexes Ir3 and Ir4 with dipyrido­[3,2-a:2′,3′-c]­phenazine (dppz) ligands can bind to DNA tightly in vitro, inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(67 citation statements)
references
References 67 publications
1
65
0
1
Order By: Relevance
“…7,12,16,35 Although a few reports have shown that these complexes can target the protein or DNA in cells, no denite SAR has been reported. 14,36,37 Iridium complexes are the most prominent ones among the metal complexes reported as theranostic anticancer agents. The cellular uptake of many drugs is usually related to their lipophilicity, while the dependence of cell penetration capabilities of iridium complexes on lipophilicity is not so obvious, and their cellular uptake mechanisms and intracellular transport pathways are largely unknown.…”
Section: Theranostic Applications Of Iridium Complexesmentioning
confidence: 99%
“…7,12,16,35 Although a few reports have shown that these complexes can target the protein or DNA in cells, no denite SAR has been reported. 14,36,37 Iridium complexes are the most prominent ones among the metal complexes reported as theranostic anticancer agents. The cellular uptake of many drugs is usually related to their lipophilicity, while the dependence of cell penetration capabilities of iridium complexes on lipophilicity is not so obvious, and their cellular uptake mechanisms and intracellular transport pathways are largely unknown.…”
Section: Theranostic Applications Of Iridium Complexesmentioning
confidence: 99%
“…It has been reported that cyclomethylated Ir(III) complexes can intercalate into mtDNA and induce mtDNA damage, followed by a decline of mitochondrial membrane potential, suppression of ATP generation, and disruption of mitochondrial energetics and metabolic status, eventually causing cancer cell apoptosis [102]. Additionally, using an mtDNA-depletion model, we found that DHODH-driven pyrimidine biosynthesis is an essential pathway which links respiration to tumorigenesis, demonstrating that DHODH could be a potential wide-spectrum target for cancer therapy [9].…”
Section: Targeting Mitochondrial Dna (Mtdna)mentioning
confidence: 99%
“…Hence, novel non-Pt (II/IV) anticancer complexes with fewer side effects are urgently required [ 9 , 10 ]. Copper(II) complexes have attracted attention in medicinal inorganic chemistry research [ 11 , 12 , 13 , 14 , 15 , 16 ]. Copper(II) is an essential micronutrient and a structural and catalytic cofactor in numerous biochemical pathways.…”
Section: Introductionmentioning
confidence: 99%